Evaluation on Site Selection of Urban Renewal Projects from the Perspective of Space Benefit: Macau Special Administrative Region as an Example - Zehui Chen; Yalong Xing; Guang Huang; JingXian Li (Journal of Mathematics)
With the advent of the stock-planning era, urban renewal has gradually become an important part of urban construction. Urban renewal is essentially a process of solving the rational redistribution of space. However, blind urban renewal can easily lead to the waste of space resources. Therefore, an appropriate renewal location can maximize the space’s renewal efficiency. Based on the perspective of space benefits, this study constructs an urban renewal site selection evaluation system suitable for Macau SAR from two aspects of social and economic benefits and space benefits and uses the DEA model to verify the evaluation system. Thus, we can more objectively and directly judge the evaluation of benefits in urban renewal site selection, maximize the efficiency of spatial renewal, and provide reference for urban site selection decisions. The results are as follows: Funing Building is the best item among the four renewal projects, and it is also the most suitable target point for development; the super-rich benefit is inefficient in terms of both space benefit and production cost benefit.